Numerical simulation study on pore clogging of pervious concrete pavement based on different aggregate gradation - Xiao, Qidan; Xia, Yapei; Zhang, Guanguan; Lin, Xiaoli; Zhao, Jun (Frontiers in Physics, 2023)
Pervious concrete (PC) pavements can effectively reduce surface runoff, but it will be clogged with time and its service life will be affected. In this study, based on three groups of PC specimens with different aggregate gradations optimized by previous experiments, the pavement-clogging simulation test is carried out using the two-way coupling of the particle flow code with computational fluid dynamics (PFC-CFD). The results show that when the gradation of aggregates in the pervious pavement is different, the volume fraction of clogging material in the pavement and the time when the volume fraction of the clogging material reaches the maximum are also different. It is related to the zigzag degree and size of the pore in the pervious pavement. The smaller the particle size of coarse aggregate in the pervious pavement, the easier it is to be clogged, and the discontinuous graded coarse aggregate has a good shielding effect on the clogging material. Different clogging material gradations have different effects on the clogging of pervious pavements. According to the aforementioned research results, researchers can select different mix ratios of anti-clogging PC according to different areas of use. The law obtained from the experiment can provide a reference for further study of the double-layer pervious pavement structure design.